2013
DOI: 10.1115/1.4025609
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Nanoparticle Margination and Adhesion Propensity in a Microchannel

Abstract: Intravenous injection of nanoparticies as drug delivery vehicles is a common practice in clinical trials of therapeutic agents to target specific cancerous or pathogenic sites. The vascular flow dynamics of nanocarriers (NCs) in human microcapillaries play an important role in the ultimate efficacy of this drug delivery method. This article reports an experimental study of the effect of nanoparticle size on their margination and adhesion propensity in microfluidic channels of a half-elliptical cross section. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…Furthermore, the fluorescence intensity profile appeared rather uniform across the channel width for all sizes of pNPs regardless of the surface coating of the microfluidic channel wall, suggesting an even distribution of pNPs, and hence the absence of margination across the channel width in our lines of analysis (see Figure S2). This was contrary to what was observed with the PA method in our study along with several other studies utilizing the adhesion method that margination occurred in the channel and its level either decreased , or increased , with size of NPs. This led us to suggest that the higher percentage of adhesion observed for smaller pNPs using the adhesion method was not due solely to the increased diffusive component leading to higher level margination because the particle distribution across the channel was uniform but was also likely attributed to the differences in the susceptibility of the pNPs to the wall shear stress.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the fluorescence intensity profile appeared rather uniform across the channel width for all sizes of pNPs regardless of the surface coating of the microfluidic channel wall, suggesting an even distribution of pNPs, and hence the absence of margination across the channel width in our lines of analysis (see Figure S2). This was contrary to what was observed with the PA method in our study along with several other studies utilizing the adhesion method that margination occurred in the channel and its level either decreased , or increased , with size of NPs. This led us to suggest that the higher percentage of adhesion observed for smaller pNPs using the adhesion method was not due solely to the increased diffusive component leading to higher level margination because the particle distribution across the channel was uniform but was also likely attributed to the differences in the susceptibility of the pNPs to the wall shear stress.…”
Section: Resultscontrasting
confidence: 99%
“…However, Toy et al and Jurney et al observed the opposite. 13,17 Given that experimental conditions might differ across studies, differences could also be attributed to the limitations in existing methods of quantifying margination. Specifically, Sobczynski et al 15 and Charoenphol et al 16 characterized the specific adhesion between the ligands on their NPs and receptors on the capturing surface as a measure of NP margination, whereas Toy et al and Jurney et al 13,17 quantified the nonspecific adhesion between their NPs and the channel walls.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Nanoparticles can be used as additives owing to their unique size-dependent properties. 27 In the current study, alumina nano-sized additives might enhance the thermal diffusivity of polyamide denture base material. Thus, its melting and injection procedure might be enhanced.…”
Section: Discussionmentioning
confidence: 72%
“…The scientific community has investigated the optimal size range, material composition, surface specific modifications, and so on for increasing the efficacy of specific drug-loaded nanocarriers. Margination dynamics, on the other hand, appeared to have been long simplified or ignored until recent years, when several studies, particularly in silico and microchannel models, attributed significance to the same [54][55][56] . Margination dynamics investigates how the shape of a nanocarrier can influence its adhesion to blood vessels and thus reduce the total site-specific deliverable 62 .…”
Section: Nano-bio Interaction-based Effects 31 Margination Dynamicsmentioning
confidence: 99%